2023
DOI: 10.1093/genetics/iyad191
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of small RNA pathways underlies germline RNA interference incompetence in wild Caenorhabditis elegans strains

Han Ting Chou,
Francisco Valencia,
Jacqueline C Alexander
et al.

Abstract: The discovery that experimental delivery of dsRNA can induce gene silencing at target genes revolutionized genetics research, by both uncovering essential biological processes and creating new tools for developmental geneticists. However, the efficacy of exogenous RNAi varies dramatically within the C. elegans natural population, raising questions about our understanding of RNAi in the lab relative to its activity and significance in nature. Here, we investigate why some wild strains fail to mount a robust RNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Secondary siRNAs are produced by an amplification machinery, for which different pools of primary siRNAs compete 15,35 , including endo-siRNAs dependent on Argonautes ERGO-1 and ALG-3/4, the genomically encoded piRNAs, and the siRNAs derived from exogenous double-stranded RNAs 13,16,[36][37][38] . Depending on the genomic and environmental contexts, genetic variation favoring one or the other primary siRNA pathway could have been selected [39][40][41][42] . Research in mammals has shown the importance of dosage of the orthologous MOV10 helicase on retrovirus silencing 43 .…”
Section: Phenotypic Effect Of the Structural Variation At Eri-6/7 On ...mentioning
confidence: 99%
“…Secondary siRNAs are produced by an amplification machinery, for which different pools of primary siRNAs compete 15,35 , including endo-siRNAs dependent on Argonautes ERGO-1 and ALG-3/4, the genomically encoded piRNAs, and the siRNAs derived from exogenous double-stranded RNAs 13,16,[36][37][38] . Depending on the genomic and environmental contexts, genetic variation favoring one or the other primary siRNA pathway could have been selected [39][40][41][42] . Research in mammals has shown the importance of dosage of the orthologous MOV10 helicase on retrovirus silencing 43 .…”
Section: Phenotypic Effect Of the Structural Variation At Eri-6/7 On ...mentioning
confidence: 99%